Influence of servant leadership on the life satisfaction of basic education teachers: the mediating role of satisfaction with job resources - Quinteros-Durand, Ronald; Almanza-Cabe, Robinson B.; Morales-García, Wilter C.; Mamani-Benito, Oscar; Sairitupa-Sanchez, Liset Z.; Puño-Quispe, Lucy; Saintila, Jacksaint; Saavedra-Sandoval, Renán; Paredes, Alcides Flores; Ramírez-Coronel, Andrés Alexis (Frontiers in Psychology, 2023)
Background Life satisfaction is essential for teachers’ work performance and student learning. Additionally, servant leadership has been shown to be one of the best leadership practices as it promotes employee well-being and satisfaction. Moreover, satisfaction with job resources acts as a mediator in the relationship between servant leadership and life satisfaction by influencing individual and collective performance in the organization. Objective This research aimed to evaluate the mediating role of satisfaction with job resources in the relationship between servant leadership and life satisfaction. Methods The study was cross-sectional and explanatory. 620 teachers aged between 20 and 62 years (M = 35 and SD = 9.49) participated in the study. Structural Equation Modeling (SEM) was used to measure life satisfaction, service leadership, and job resource satisfaction through the use of questionnaires. Results The results indicated that the model obtained an adequate fit, χ2 = 2,658, df = 551, p < 0.001, CFI = 0.941, TLI = 0.936, RMSEA = 0.079, SRMR = 0.070. The results confirm the positive influence of leadership on satisfaction with resources and life satisfaction. Additionally, a positive influence of satisfaction with job resources on life satisfaction was observed. Moreover, the mediation of job resources in servant leadership and life satisfaction was confirmed. Conclusion Servant leadership, supported by satisfaction with job resources, can reduce effort and associated costs, stimulate personal growth and learning, and improve the well-being of teachers.